2021
DOI: 10.3390/nu13030960
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Changes in Gastric Cancer Patients during Preoperative FLOT Therapy: Preliminary Results of an Italian Cohort Study

Abstract: Background: The impact of the new chemotherapy, fluorouracil plus leucovorin, oxaliplatin, and docetaxel (FLOT) on body composition in gastric cancer (GC) patients remains unknown. We assessed body composition changes of GC patients receiving the FLOT regimen and their impact on treatment outcomes. Methods: Preoperative pre- and post-FLOT computed tomography (CT) scans of advanced GC patients were studied. Lumbar skeletal muscle index (SMI) and adipose indices were calculated before and after FLOT. Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
(62 reference statements)
3
15
0
Order By: Relevance
“…This study is affected by several limitations: i) the sample size needs to be increased to confirm our findings; ii) since changes in body composition during chemotherapy administration are frequently reported [ 45 ], [ 46 ], [ 47 ], further longitudinal analysis is planned to investigate the impact of repeated PIPAC cycles; iii) GI primary tumors may differently condition nutritional status of PM patients.…”
Section: Discussionmentioning
confidence: 97%
“…This study is affected by several limitations: i) the sample size needs to be increased to confirm our findings; ii) since changes in body composition during chemotherapy administration are frequently reported [ 45 ], [ 46 ], [ 47 ], further longitudinal analysis is planned to investigate the impact of repeated PIPAC cycles; iii) GI primary tumors may differently condition nutritional status of PM patients.…”
Section: Discussionmentioning
confidence: 97%
“…Although the number of patients included in our single center-cohort exceeded the number of patients in the abovementioned analyses (Mirkin et al 2017;Rinninella et al 2021), the sample size (n = 46) as well as the number of events (disease recurrence/death: n = 14) are a limitation of this study. Furthermore, the follow-up period (median: 32 months) was shorter in comparison to the FLOT4 study (43 months), therefore, the impact of body composition parameters and dynamics on clinical outcome has to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported that LSMM might be an unfavorable factor for the short-time outcomes and prognosis ( 19 22 ), but some existing have shown contrasting results ( 23 26 ). Katsunobu et al ( 23 ) have shown that there is no relationship between preoperative LSMM and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%